DEVELOPING SOFT SKILLS THROUGH GAMIFIED ENGLISH LANGUAGE ACTIVITIES (ZOMBIE CHALLENGE SERIES) - Idek, Sirhajwan (PEOPLE: International Journal of Social Sciences, 2019)
The goal of this study was to explore the effects of gamification on a short course that aimed to develop soft skills among students of a vocational school in Sabah. English language was used as the medium of instruction during the task and four target grammatical forms were integrated into the gamified context: sequence connectors, conditionals, modal verbs and sentence construction. The gamified context consisted of four levels where the students were expected to solve the challenge before moving to the next level. The gamified activities were named “Zombie Challenge Series” since its narrative derived from the popularity of zombie in the entertainment and technology industry. There were several game elements that were incorporated into the task. The students were interviewed in order to elicit their perception related to the gamified activities. The findings showed that the students became more aware of the linguistic features that they were expected to use and the cognitive skills needed to solve the challenges. They became more motivated to learn and they were able to develop their soft skills better.